Effects of Different Tactile Feedback on Myoelectric Closed-Loop Control for Grasping Based on Electrotactile Stimulation - Xu, Heng; Zhang, Dingguo; Huegel, Joel C.; Xu, Wendong; Zhu, Xiangyang (IEEE transactions on neural systems and rehabilitation engineering, 2016)
Closed-loop control is important for amputees to manipulate myoelectric prostheses intuitively and dexterously. Tactile feedback can help amputees improve myoelectric control performance for grasping objects. To investigate the effects of different tactile feedback, we performed experiments on six amputees and six able-bodied subjects via electrotactile stimulation. Using a virtual environment, six kinds of objects with different weights and stiffnesses were used for grasping tasks. Five feedback conditions (no feedback, pressure feedback, slip feedback, pressure + slip feedback, and vision feedback) were considered. Nine evaluation indexes and three control objectives (rapidity, economy, and stability) were proposed. Under the five feedback conditions, our study investigated four issues: 1) three types of grasping-related failures; 2) four types of grasping-related time measures; 3) average grasping force; 4) standard deviation of the grasping force. Results indicate that: 1) slip feedback is better than pressure feedback; 2) pressure + slip feedback can improve grasping rapidity; 3) slip feedback significantly contributes to grasping economy and stability; and 4) pressure + slip feedback can perform as well as vision feedback.